Analisis kinerja manajemen pengunjung di destinasi wisata bandung utara menggunakan importance-performance analysis - Widiyanti, Rikantini; Mandasari, Virginia; Gabriela, Elisabet; Chendraningrum, Dinarsiah (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2025)
The increase in visitor numbers during holidays has positive implications for the tourism business; however, it can also lead to negative impacts such as overcrowding, increased pollution, vandalism, and potential disorder. These negative consequences may affect visitor satisfaction, comfort, convenience, and safety. Therefore, the implementation of visitor management is necessary as a proactive measure to create a better holiday experience. This study adopts a quantitative approach using a questionnaire distributed to respondents. The questionnaire includes statements evaluating the performance of tourist destinations in Bandung and the importance of these statements from the visitors' perspectives. The collected data is analyzed using the Importance-Performance Analysis (IPA) technique with the aid of SPSS version 26. IPA is used to assess and evaluate the performance of destination managers by comparing the importance of various attributes of a product or service (i.e., the tourism experience) with visitors' perceptions of how well these attributes meet their expectations. This study aims to explore and understand the effectiveness of visitor management in addressing challenges caused by visitor surges and the extent to which visitor satisfaction can be achieved through the implementation of appropriate management strategies.